Arbitrase dalam Penyelesaian Sengketa Klaim Biaya Konstruksi Akibat Perpanjangan Waktu: Studi Hukum Perjanjian di Indonesia - Indahwati, Amaliyah Noor; Sami’an, S.; Hardjomuljadi, Sarwono (SIGn Jurnal Hukum, 2024)
This research aims to analyze the resolution of construction cost claim disputes arising from time extensions, focusing on the arbitration mechanism. The findings indicate that delays in the completion of construction projects not only give rise to cost claim disputes but also necessitate a meticulous analysis of the causes of the delays and the responsibilities of the parties involved. In this regard, arbitration offers a more effective and efficient dispute resolution mechanism than litigation. The advantages of arbitration, including the speed of the process, confidentiality, expertise of arbitrators, procedural flexibility, and binding awards, make it a favourable option for the parties. Therefore, the parties must pay close attention to the arbitration clause in the construction contract. This clause must be formulated clearly and definitively, encompassing the types of construction cost claim disputes arising from time extensions, including claims for price adjustment, overhead costs, extension of performance bonds, material demurrage, and equipment idleness. In addition, the parties can also utilize the Binding Opinions of the BANI Arbitration Center as an instrument for dispute prevention and resolution. For information, Binding Opinions have binding legal force on the parties and are enforceable through the District Court. Thus, the Binding Opinions of the BANI Arbitration Center are beneficial as a dispute resolution instrument and contribute to the development of legal scholarship.